1992
DOI: 10.1002/j.2161-007x.1992.tb00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Brief Christian and Non‐Christian Rational‐Emotive Therapy With Depressed Christian Clients: An Exploratory Study

Abstract: The current outcome study operationalized a brief"Christian" form of rational-emotive therapy (CRET)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 33 publications
2
75
1
1
Order By: Relevance
“…29,30 However, 3 studies have shown no difference in using religious imagery as an adjunctive to therapy for depressed patients. [31][32][33] An appropriate study remains to be conducted among the urban poor.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 However, 3 studies have shown no difference in using religious imagery as an adjunctive to therapy for depressed patients. [31][32][33] An appropriate study remains to be conducted among the urban poor.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies (Gibbel, 2011;Rosmarin, 2010) used computer-delivered therapy, four (Azhar and Varma, 1995;Azhar et al, 1994;Barron, 2007;Bowland et al, 2012) used face-to-face group sessions and ten (Akuchekian et al, 2011;Armento et al, 2012;Ebrahimi et al, 2013;Johnson and Ridley, 1992;Johnson et al, 1994;Pecheur and Edwards, 1984;Propst et al, 1992;Razali et al, 2002;Razali et al, 1998;Zhang et al, 2002) provided individual face-to-face sessions. There was no significant difference between the average length (in weeks) or duration (in minutes) of F-CBT provided in group settings, compared with individual sessions.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The two studies reporting use of computer-delivered therapy (c-CBT) had very high levels of attrition: one (Gibbel, 2011) reported over three times the levels of attrition from the standard c-CBT group (46%) compared with faith-adapted c-CBT (13%), and the other (Rosmarin, 2010) recorded that 66% of participants dropped out of the study before (2007) Used religious beliefs and practices to support religious coping skills. Johnson (1992Johnson ( , 1994 Used biblical teachings to dispute irrational beliefs; emphasised prayer and Christian content within therapy. Pecheur (1984) Used religious and biblical teachings to challenge negative cognitions.…”
Section: Blindingmentioning
confidence: 99%
See 2 more Smart Citations